MEWUJUDKAN PELAYANAN PRIMA ADMINISTRASI KEPENDUDUKAN MELALUI INOVASI PROGRAM KALIMASADA KOTA SURABAYA - Uswatun Hasanah; Vidya Imanuari Pertiwi (Peneliti.net, 2023)
KALIMASADA Program (Civil Administration Aware Community Neighborhood Area) is an innovation from the Surabaya City Population and Civil Registration Office which aims to improve Civil Administration services for Surabaya City residents. Optimization of KALIMASADA program will be achieved when the administration service itself can be carried out in an excellent service. Against this background, this study aims to analyze the implementation of KALIMASADA program's excellent service at Rungkut Tengah Office. The qualitative research method forms the basis for the procedure for conducting this research, where the author then obtains data through interviews as well as the results of observations during the research period at the Rungkut Tengah Office. The results of the study indicate that there are still two principles of excellent service that cannot be fulfilled in the implementation of the KALIMASADA program at the Rungkut Tengah Office. Thus, it can be concluded that the implementation of the KALIMASADA program at the Rungkut Tengah Village Office is still not optimal because the two principles of excellent service have not been fulfilled, namely service that exceeds residents' expectations and service that prioritizes quality.